2021
DOI: 10.3390/molecules26102947
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intra-Molecular Organocatalysis of SN2 Fluorination by Crown Ether: Kinetics and Quantum Chemical Analysis

Abstract: We present the intra- and inter-molecular organocatalysis of SN2 fluorination using CsF by crown ether to estimate the efficacy of the promoter and to elucidate the reaction mechanism. The yields of intramolecular SN2 fluorination of the veratrole substrates are measured to be very small (<1% in 12 h) in the absence of crown ether promoters, whereas the SN2 fluorination of the substrate possessing a crown ether unit proceeds to near completion (~99%) in 12 h. We also studied the efficacy of intermolecular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Hence, the rate constant of the reaction increased due to a decrease in Gibbs free energy of activation. [32] In 2021, Xu and co-authors reported the nucleophilic fluorination of alkyl substrates (35) using KF and an unbalanced ion-pair promoter (36), i. e., a bulky and charge-delocalized cation and a small and charge-localized anion (Scheme 17). In an unbalanced ion pair, due to the large size of the cation, the affinity between the cation and the anion is relatively small.…”
Section: Dr Gangotri Pemawat Is Presently Working As An Assistant Pro...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the rate constant of the reaction increased due to a decrease in Gibbs free energy of activation. [32] In 2021, Xu and co-authors reported the nucleophilic fluorination of alkyl substrates (35) using KF and an unbalanced ion-pair promoter (36), i. e., a bulky and charge-delocalized cation and a small and charge-localized anion (Scheme 17). In an unbalanced ion pair, due to the large size of the cation, the affinity between the cation and the anion is relatively small.…”
Section: Dr Gangotri Pemawat Is Presently Working As An Assistant Pro...mentioning
confidence: 99%
“…behaved as an extra Lewis base binding the counter cation K + and diminished the strong Coulombic force on F − . Hence, the rate constant of the reaction increased due to a decrease in Gibbs free energy of activation [32] …”
Section: Aliphatic Nucleophilic Fluorinationmentioning
confidence: 99%
“…Generally, this is undesirable for radiofluorination, as 18 F possesses a relatively short half-life of 109.77 min. Various non-radioactive nucleophilic fluorination methods [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ] have been developed using various phase-transfer catalysts (PTCs) for their application in radiopharmaceutical chemistry in which hydrogen bonding between protic PTC and nucleophile [ 18 F]fluoride enhances the reaction and selectivity [ 36 , 37 ]. The recent development of tri-( tert -butanol)-methylammonium [ 18 F]fluoride (TBMA- 18 F) [ 13 ] as a promoter for radiofluorination demonstrated an excellent [ 18 F]fluoride elution efficiency under the reduced basicity of [ 18 F]fluoride, with moderate to good obtained RCYs.…”
Section: Introductionmentioning
confidence: 99%
“…Shinde and co-workers proposed that these excellent organocatalytic properties of the counter-cation may be attributed to the coordinating capacity of the two functional groups (ammonium and hydroxyl) in TBMA + . This rate enhancement, promoted by the counter-cation, which would be the first such example for 18 F-fluorination, exhibits significant advantages over more conventional methods using alkali metal cations, M + (M = K, Rb, Cs), because in the latter case the Lewis base promoters such as bulky alcohols [ 8 , 32 ], oligoethylene glycols [ 8 , 31 , 32 ], ionic liquids [ 8 , 33 ], or crown ethers [ 34 , 35 ] are required to suppress the harmful Coulomb forces of the counter-cation on the nucleophile.…”
Section: Introductionmentioning
confidence: 99%